Morphological and Functional Aspects of Cellular Hemostatic Mechanisms - White, J. G. (Hämostaseologie, 1996)
Transmission, scanning and low-voltage, high resolution scanning electron microscopy have provided fundamental knowledge of relationships between plate-let structure and function. In combination with ultrastructural cytochemistry and immunocytochemistry, basic aspects of shape change, pseudopod extension, internal transformation, secretion, adhesion, aggregation, spreading, hemostatic plug formation and thrombus development have been defined. The morphological events of the platelet reaction in hemostasis have been linked to biochemical alterations. The result is a comprehensive picture of cellular aspects of hemosta-sis. This knowledge provides a basis for designing programs of treatment for heart attacks, strokes and other occlusive vascular disorders, as well as for their prevention.
Keywords: Adhesion; contraction; secretion; receptors; actin; myosin